Structural demography and growth patterns of Scirpus grossus L. / Ali Abdullah Majrashi - Majrashi, Ali Abdullah (2014)
Scirpus grossus L. is a principal rhizomatous weed in the rice fields, drainage and irrigation canals, river banks, abandoned rice fields and wasteland in Malaysia. This study describes the modular dynamics, spatio-temporal growth patterns of aerial plant and sub-terranean rhizome populations of this scourge on fertilized and unfertilized peat and paddy soils. The NPK fertilizer application at 100:30:30 ha-1 resulted in more robust aerial plant growth with ca. 253.5 ramets m-2 (mean dry aerial biomass of 23.2 g plant-1) compared with 235.6 ramets m-2 (16.3 g plant-1) in unfertilized peat soils24 weeks after planting of the mother plant. The parallel figures for plants growing on paddy soils of the Jawa series were ca. 97.08 ramets m-1 (12.19 g plant-1)(fertilized paddy soils) and 83.67 ramets m-1 (10.89 g plant-1) (unfertilized paddy soils) 24 weeks after planting of the mother plant. Mean ramets mortality was significantly higher in unfertilized paddy soils at 121.3 ramets m-2, while in the fertilized paddy soils this was only 34.7 ramets m-2, resulting respective net populations of ca. 218.8 ramets m -2 and 114.3 ramets m -2 in fertilized and unfertilized plots. In paddy soils mean ramets mortality in unfertilized paddy soils was ca. 8.58 ramets m-2, while this was only ca. 5.67 ramets m-2, leading to the respective resultant net populations of 91.41m-2 and 75.09 ramets m-2. Flowering set in earlier among ramets in fertilized peat soils with 103.2 ramets m-2 vis-a-vis 77.5 ramets m-2, 24 weeks after transplanting of the mother plant in unfertilized soil. Flowering set in earlier among ramets in fertilized paddy soils with 49.56 ramets m-2vis-a-vis the unfertilized soil registering ca. 47.79 ramets m-2, 24 weeks after transplanting of the mother plant. Fertilizer applications to either peat or paddy soils did not register any significant difference in mean plant height, chlorophyll contents, and chlorophyll fluorescence measurements vis-a-vis those plants devoid of fertilizer application. No measurable differences were registered in rhizome lengths over time of S. grossus plants devoid of fertilizer application compared with those growing in fertilized peat soils. Similarly patterns were observed among S. grossus populations in both fertilized and unfertilized paddy soils. The time- and space-mediated clonal growth of S. grossus did not register any significant preferential directionality and dispersion of aerial plants and their sub-terranean rhizomes irrespective of fertilizer application or soil types, but rather displaying opportunistic resource capture by aerial and sub-terranean modules. ANOVA and Tukey’s HSD tests, response surface, fractal dimension and fractal topography analysis under fertilizer application factor and differences soils (peat soils - paddy soils) were used in the study from the first week to the 24th week. Dispersion analyses of rhizomes was also employed. In circular statistics r (concentration), s (angular deviation), Rayleigh’s R and Rayleigh’s z were computed on the emerged ramets of S. grossus. Results of Rayleigh’s z test showed significant mean direction of ramets emergence for all replicates in the fertilized plots (p > 0.01). Significant mean direction was obtained only for replicate R1 for the unfertilized plots. No significant mean direction for replicates R2 and R3 of the unfertilized plots means that ramets emergence is distributed uniformly around the circle, that is originating from the mother plant. They occur when s, the dispersion given by the angular deviation is near the maximum (where 0 < s < 83.01). Dispersion analysis of ramets by circular statistics on S. grossus generated no special preferences in the direction of modules or emerged ramets as explained by the Rayleigh’s r, Rayleigh’s z, and mean angle of dispersion in pest and paddy soils. However, there were heavier concentrations of ramets in the eastern sector of the plot, presumably due to phototropic effect of sunlight. In response surface analyses in peat soils results showed the stationary points obtained for the unfertilized plots is at x-distance = 0.03 m, y-distance = - 0.06 m and time (t) = 9.8 months. This function predicted a maximum density of 178 plants m-2 to occur at the location and time. For the fertilized plot, the stationary point is at x-distance = 0.20 m, y-distance = -0.82 m and t = 11.31 months. The predicted density obtained was 291.02 plants m-2. While in paddy soils the best location and time in unfertilized soil was between x- distance 0.00 m and y- distance -0.14 m at t = 8.16 month, while in fertilized soil the location was between x- distance -0.13 m and y- distance 0.20 m and the best time at t = 8.48 month. In fractal topography analysis results showed value fractal dimension from gl=0 – gl=100 between area-covering and ranched network (1<D> 2). The area-covering concentrated at gl=0 and gl=40 in both peat and paddy soils (fertilized and unfertilized). While after gl=100 – gl=255 sporadic distribution (D- 0) in peat (fertilizer and unfertilized) and unfertilized paddy soils. While for fertilized paddy soil, gl=100 – gl=255. The fractal dimension analysis method allows the structural complexity of such associations to be compared between plant communities, with regard to their potential for soil resource acquisition and utilization. In peat soil, distinct and partly not significant differences are found (fractal dimension between 1.52 ± 0.53 and 1.50 ± 0.59) in unfertilized and fertilized plots. In paddy soil, fractal dimension between 1.53 ± 0.55 and 1.52 ± 0.49) in unfertilized and fertilized plots. We found distinct and partly not significant differences between plant in peat and paddy soils, when analysing many small units of a complex root system association. In larger plant communities, a broad variety of below-ground structures are recorded in its entirety, integrating the specific features of single sub-structures. In that way, extreme fractal dimensions are lost and the diversity decreases. Therefore, the analysis of larger units of root system associations provides a general knowledge of the complexity of root system structures for heterogeneous plant communities. Under the prevailing experimental conditions in the studies, the following conclusions can be drawn, viz: (i) The optimal period of clonal growth for Scirpus grossus, in general was between 10-18 weeks after planting; (ii) Augmentation with different NPK fertilizer concentrations and at different water depths had the following effects on S. grossus growth in both fertilized and unfertilized peat and paddy soils, (a) Increased rate of natality and the population number of ramets, fortified by enhanced proliferation of subterranean rhizomes; (b) Decreased rates of ramets mortality; (c) Increased rate and production of inflorescence of the weed; and (d) Enhanced production of biomass vis-a-vis the control of various plant components. However, the NPK fertilizer treatment did not have a significant impact on the plant height; chlorophyll content; and chlorophyll fluorescence, registering non-significant difference in both fertilizer and control plants; (iii) Fertilizer concentration with water depth did have a significant impact on the following parameters; namely (a) plant height; and (b) inflorescence number; (iv) Aerial modular growth, dispersion, response surface, plant topography-fractal analyses on emerged ramets, and fractal dimension boxing analyses of subterranean rhizome modules confirmed that the fertilizer treatment (at NPK 100:30:30) did not have a significant and prevalent impact on the growth patterns of S. grossus.